Proxy Response Heterogeneity to the Indian Monsoon During Last Millennium in the Himalayan Region - Roy, Ipsita; Tomar, Nidhi; Ranhotra, Parminder Singh; Sanwal, Jaishri (Frontiers in Ecology and Evolution, 2022)
We reviewed the available climate records for the past two millennia based on the analyzed sediment and speleothem archives from different regions of South Asia. Speleothem records from the core-monsoon regions of the Indian sub-continent have revealed the Little Ice Age (LIA) as a climatically dry phase, whereas the same from the western and central Himalaya recorded LIA as wet. Moreover, the sediment-derived vegetation proxy records (pollen-spores and stable organic carbon isotope (δ13Corg)) from the western Himalaya also reported LIA as a dry phase. Heterogeneous results by different proxies during LIA enhanced our interest to understand the response of the proxies towards the two primary precipitation sources viz. Indian summer monsoon (ISM) and winter westerly disturbances (WDs), over the Himalaya. We emphasize that in the Himalayan region, the vegetation predominantly responds to the ISM dynamics, whereas speleothem also captures the WD effect.